Pengaruh Merek, Harga dan Kualitas Produk Terhadap Keputusan Pembelian Baju Bekas (Thrift) di Kota Bima - Nunung Anjani; Muhajirin Muhajirin; Muhammad Badar (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to research consumer purchase decisions on used clothes (thrift) in Bima City. Thrifting is an activity of shopping for used products, which is considered to have a cheaper price and is considered more economical, so that many people tend to buy these thrift clothes, by spending minimal cost a person can get goods with various models and even quality branded goods can be found. This research was conducted in the city of Bima. This study uses associative research and research instruments using a questionnaire with a Likert scale. The population of this study is all thrift users in Bima City. The number of respondents in this study was 100 respondents. The data collection techniques used are observation, questionnaire, and literature review. The data obtained was processed using SPSS data processing tools. From the results of the research, it is known that brands have a significant effect on the decision to buy used clothes (thrift), price does not have a significant effect on the decision to buy used clothes (thrift). Product quality has a significant effect on purchasing decisions (thrift). Simultaneously, the brand, price and quality of the product have a significant effect on the decision to buy used clothes (thrift).